(3Ce GdHQGgjfs - (3GdSfhSj GdMSfj, CHh YHO Gddg, eMeO Hf jhSa Hf YeQ Hf TYjH, J (B895 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI hGdSdGe Ydi QShd Gddg GYde Cf GdMce GdYbdj jfMUQ aj KdGKI CbSGe(B: (3GdhLhH, hGdGSJMGdI, hGdLhGR aGdhGLH eG dG ojJUhQ aj GdYbd YOeg hGdeSJMjd eG dG ojJUhQ aj GdYbd hLhOg (B...s
(3BNQgG (B:s
(3abO HGf dc JVeof cdeJj GdTgGOI eY bdI MQhagG dLejY eG jLH Ydi Gdecda eYQaJg ef YbGFpO GdEjeGf aj Mbg JYGdi haj Mb QSdg Ydjge GdUdGI hGdSdGe dYdgG dGNJUGQgG eY GTJeGdgG Ydi eG PcQfGg LYdgG GdTQY JQLeI Ydi eG aj GdbdH ef GdESdGe Jes
(3JHUQI GdYfhGf (B:s
(3YbjOI GdSfhSj GdUZQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\154s
(3cTa GdXfhf (B1\170s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds